Potential of Ascidians as Extractive Species and Their Added Value in Marine Integrated Multitrophic Aquaculture Systems–From Pests to Valuable Blue Bioresources - Marques, Luisa; Calado, Ricardo; Lillebø, Ana Isabel (Frontiers in Marine Science, 2022)
Ascidians are considered as filter-feeder biofouling pests that negatively affect aquaculture facilities. However, they can also be recognized as a potential co-cultured/extractive species for integrated multi-trophic aquaculture (IMTA) with potential added value as bioresources. A systematic review aiming to understand the ecological importance of ascidians as efficient filter-feeders [What?]; their potential contribution as extractive species [How?]; and to set the benchmark for their nutritional value and potential added value to the aquaculture industry [For what?] is a timely contribution to advance the state of the art on these largely overlooked bioresources. In the last two decades, there has been an overall increase in publications addressing ascidians in aquaculture, namely, their negative impacts through biofouling, as well as their role in IMTA, environmental status, and microbiology. While Ciona intestinalis, a solitary ascidian, has been the most studied species, overall, most ascidians present high filtration and fast-growth rates. As ascidians perform well under IMTA, competition for resources and space with other filter-feeders might occur, which may require additional management actions to optimize production. Studies addressing their bioactive products show that ascidians hold great potential as premium ingredients for aquafeed formulations, as well as dietary supplements (e.g., amino acids, fatty acids). Further research on the potential use of ascidians in IMTA frameworks should focus on systems carrying capacity.